Peri-Ictal Autonomic Control of Cardiac Function and Seizure-Induced Death - Wenker, Ian C.; Blizzard, Elizabeth A.; Wagley, Pravin K.; Patel, Manoj K. (Frontiers in Neuroscience, 2022)
Sudden unexpected death in epilepsy (SUDEP) accounts for the deaths of 8 to 17 % of patients with epilepsy. Although the mechanisms of SUDEP are unknown, one proposed mechanism is abnormal control of the heart by the autonomic nervous system (ANS). Our objective was to determine whether the broad changes in ictal heart rate experienced by mouse models of SUDEP are 1) due to the ANS and 2) contribute to seizure-induced death. Seizures were induced by electrical stimulation of the hippocampus of a mouse carrying the human SCN8A encephalopathy mutation p.Asn1768Asp (N1768D; “D/+ mice”). Using standard autonomic pharmacology, the relative roles of the parasympathetic and sympathetic nervous systems on heart rate changes associated with seizures were determined.All induced seizures had pronounced ictal bradycardia and postictal tachycardia. Seizure susceptibility or severity were unchanged by the pharmacological agents. Administration of Atropine, a muscarinic antagonist, eliminated ictal bradycardia, while carbachol, a muscarinic agonist, had no effect on ictal bradycardia, but reduced postictal tachycardia. Sotalol, an adrenergic β-receptor antagonist, had no effect on ictal bradycardia, but did suppress postictal tachycardia. Isoproterenol, a β-receptor agonist, had no effect on either ictal bradycardia or postictal tachycardia. Administration of the 1-receptor antagonist prazosin increases the incidence of seizure-induced death in D+ mice. Although postictal heart rate was lower for these fatal seizures in the presence of prazosin, rates were not as low as that recorded for carbachol treated mice, which all survived. Both ictal bradycardia and postictal tachycardia are manifestations of the ANS. Bradycardia is mediated by a maximal activation of the parasympathetic arm of the ANS, and tachycardia is mediated by parasympathetic inactivation and sympathetic activation. While the changes in heart rate during seizures are profound, suppression of postictal heart rate did not increase seizure mortality.